Evaluation of RapidSTAT®, DrugWipe® 6S, DrugScreen® 5TK and DrugScreen® 7TR for on‐site drug testing in German police roadside traffic patrol. Issue 8 (1st April 2022) - Liut, Jennifer; Bott, Ulrich; Madea, Burkhard; Krämer, Michael; Maas, Alexandra
Abstract: Driving under the influence of drugs (DUID) remains a subject of concern worldwide, and its increasing trend is likely to continue. Therefore, there is a constant need for reliable on‐site drug tests to identify drugged drivers during roadside patrols. Performance and reliability of four on‐site drug tests were evaluated among a high number of DUID cases in Germany. Results of oral fluid (OF) (RapidSTAT® and DrugWipe® 6S) and urine (DrugScreen® 5TK and 7TR) test devices were compared with corresponding serum/plasma results obtained by confirmation analyses in consideration of recommended analytical limits for substances pertaining the annex of the German Road Traffic Code ('Straßenverkehrsgesetz', StVG) s. 24a (2). Overall, the screening devices performed well for individual drugs; however, none of the test devices assessed in this study fulfilled the ROSITA‐1 criteria (sensitivity, specificity ≥ 90% and accuracy ≥ 95%) for all substances. Our data demonstrated that both urine tests showed high sensitivities for most compounds. DrugWipe® 6S (94%) and RapidSTAT® (93%) revealed high sensitivities, especially for amphetamine screening. Poor specificities (<90%) and accuracies (<95%) were observed for all tests except for low‐prevalent substances (e.g., opiates). For drug testing in OF, Δ 9 ‐tetrahydrocannabinol (THC) still seems to be a compound of concern due to poor sensitivity (RapidSTAT®, 77%; DrugWipe® 6S, 85%), although the results indicate improvements compared with previously reported data. Although the obtained data indicate reliable detection for some substances, deployment of trained police officers is inevitable to identify DUID suspects by signs of recent use and recognising impairment. Abstract : Performance of four on‐site drug screening devices (oral fluid vs. urine) were evaluated in context with German DUID cases between 2012 and 2018. Overall, the screening devices performed well for individual drugs; however, none of the test devices assessed in this study fulfilled the ROSITA‐1 criteria (sensitivity, specificity ≥ 90% and accuracy ≥ 95%) for all substances. Even though the results for the test devices were mostly adequate, deployment of trained police officers is inevitable to identify DUID suspects.